Evaluacion de la capacidad alelopatica del mastuerzo (Lepidium virginicum Lin.) sobre lechuga y arroz - Garcia, R.C.=700 1 Paredes, E.; La O, F.
(Es, En)
Ilus., 12 ref.
Keywords: LEPIDIUM; ALELOPATIA; LACTUCA SATIVA; ORYZA SATIVA; CUBA; LEPIDIUM VIRGINICUM